2018
DOI: 10.3171/2018.4.focus18122
|View full text |Cite
|
Sign up to set email alerts
|

Bridging veins and veins of the brainstem in microvascular decompression surgery for trigeminal neuralgia and hemifacial spasm

Abstract: OBJECTIVEIn microvascular decompression surgery for trigeminal neuralgia and hemifacial spasm, the bridging veins are dissected to provide the surgical corridors, and the veins of the brainstem may be mobilized in cases of venous compression. Strategy and technique in dissecting these veins may affect the surgical outcome. The authors investigated solutions for minimizing venous complications and reviewed the outcome for venous decompression. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…This emphasizes the worth of preoperative and intraoperative evaluations of the whole SPVC rather than the main SPV(s) only [11]. The TPv was the most common offending vein, similar to previous reports [8,32]. Corresponding intraoperative photographs of the same case.…”
Section: Spvc and Disturbance Of The Operative Fieldsupporting
confidence: 86%
See 1 more Smart Citation
“…This emphasizes the worth of preoperative and intraoperative evaluations of the whole SPVC rather than the main SPV(s) only [11]. The TPv was the most common offending vein, similar to previous reports [8,32]. Corresponding intraoperative photographs of the same case.…”
Section: Spvc and Disturbance Of The Operative Fieldsupporting
confidence: 86%
“…This is because of the very medial course of the TPv and medial type III drainage of the SPV 3 into the SPS beyond the microsurgical field. ALMv anterior lateral marginal vein, bFFE balanced fast field echo, CPA cerebellopontine angle, SCA superior cerebellar artery, SPV superior petrosal vein, SPVC superior petrosal vein complex, SPV1 first SPV, SPV2 second SPV, SPV3 third SPV, TG trigeminal nerve, TPv transverse pontine vein, v.CPF vein of cerebellopontine fissure, v.MCP vein of the middle cerebellar peduncle Although SPVC components commonly block the surgical exposure, preserving it is possible in many cases by utilizing adequate cisternal drainage and careful development of intervenous corridors [8,9,11,32]. This proved to be effective in the cases reviewed in this study.…”
Section: Spvc and Disturbance Of The Operative Fieldmentioning
confidence: 99%
“…[1,13,14,20,21,23,27,31] Venous compression of the root of the facial nerve is rare in HFS and the veins alone as offending vessels are reported in 0%-7.9%. [8,10,[28][29][30]33] It was shown that cure rates in HFS and trigeminal neuralgia patients who had arterial and venous compressions were significantly lower compared to those with arterial compression alone. [28] Jannetta first described small arteriole in contact and a minute venule crossed the caudal aspect of the facial nerve REZ.…”
Section: Discussionmentioning
confidence: 99%
“…[8,10,[28][29][30]33] It was shown that cure rates in HFS and trigeminal neuralgia patients who had arterial and venous compressions were significantly lower compared to those with arterial compression alone. [28] Jannetta first described small arteriole in contact and a minute venule crossed the caudal aspect of the facial nerve REZ. e arteriole was mobilized and held away with shredded Teflon, and the venule considered as true causative vessel was coagulated and divided, and patient's HFS slowly disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation